SENYAWA BIOAKTIF DARI DAUN MIANA SEBAGAI KANDIDAT PENGHAMBAT BETA-LAKTAMASE: STUDI KOMPUTASI - Moulana, Mohammad Zaeni; Rusdin, Agus; Lestari, Mila Ayu; Fathin, Nayla Maymuna; Oktaviana, Lina; Novitasari, Dhania (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Antibiotic resistance occurs through several mechanisms, one of which is increase in beta-lactamase which can inactivate beta lactam antibiotics. The approach in finding new sources of antibiotics can be done by utilizing natural resources, one of which could be developed is miana leaves (Coleus scutellarioides). However, there has been no evaluation study related the antibacterial potential of the bioactive content miana leaves against beta-lactam. This study analyzed the potential of bioactive compounds from miana leaves as beta-lactamase inhibitors through a computational approach. The methods used include physicochemical and pharmacokinetic profile prediction analysis, followed by pharmacophore screening and molecular docking. The results showed that most of the bioactive compounds of C. scutellarioides fulfill Lipinski's rule and show a good ADMET profile. Pharmacophore analysis produced the best model with an area under curve (AUC) score of 0.87. Molecular docking studies showed the compound 1-(4-phenylcyclohexyl)-1-hexanone had the highest binding affinity to beta-lactamase with a binding energy of -7.2 kcal/mol. This molecular interaction involves hydrogen bonding with amino acid residue GLU272 and van der Waals interaction toward ALA292 and TYR150. Therefore, bioactive compounds from miana leaves show potential as beta-lactamase inhibitors and open opportunities for the development of new antibacterial therapies based natural resources.